Unraveling the Impact: Esteh Indonesia's Crisis Responsibility on Consumer Loyalty in Yogyakarta - Nadhelita, Chika; Haq, Mochammad Fauzul; Fatonah, Siti (Jurnal Paradigma, 2025)
This study examines the impact of Esteh Indonesia's crisis responsibility on consumer loyalty in Yogyakarta. Crisis responsibility refers to corporate efforts to manage crises and improve public perception, influencing consumer loyalty. Using a quantitative approach, data was collected via questionnaires, literature, and documentation from 100 respondents. Analysis with SPSS 25 showed a strong correlation (0.907) between crisis responsibility and loyalty, with an R² value of 82.3%. Hypothesis testing confirmed a significant effect, with thitung(21.323)>ttabel(1.987)thitung(21.323)>ttabel(1.987), proving that Esteh Indonesia's crisis management efforts positively impact consumer loyalty.